Literacy Studies: Implementation of Problem-based Learning Models to Improve Critical Thinking Skills in Elementary School Students - Smith, George; Amirudin Ichda, Mochammad; Alfan, Muhammad; Kuncoro, Tri (KnE Social Sciences, 2023)
Students often have difficulty in developing critical thinking skills and creative thinking in problem-solving and applying concepts learned in school. The difficulty is due to weak understanding of concepts, especially for students who are in the low category; therefore, it has an impact on the low-student learning outcomes. One of the reasons for the low-learning outcomes is the difficulty in understanding a concept given by the teacher so students tend to be passive in learning activities, which has an impact on the lack of students to think both critically and creatively in applying the concepts of the material provided by the teacher. The purpose of this study is to conceptually analyze the use of problem-based learning models to improve critical thinking skills in elementary school students. The research method used in this study is a systematic literature study. The author selected 25 articles from journals and articles published during the last 10 years from 2012 to 2022. The results of this review can improve student learning outcomes in elementary schools because this model has characteristics suitable to be applied in real-life situations; in avoiding simple answers, and allowing for multiple solutions to the situation. Keywords: Problem-based learning, critical thinking skills